Pengaruh Rendahnya Pemahaman Fungsi Manajemen SDM, Terhadap Kinerja Karyawan: (Studi Kasus Yayasan Al-Ghufron Pamekasan) - Akhmad Fawaid; Fahrurozi Fahrurozi (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2020)
The low understanding of the functions of Human Resources management, affects the weak performance of employees. As a result, it has an impact on the wheels of the organization in the Al-Ghufron Pamekasan Foundation. So to find out how much, the effect caused, research needs to be done. This study uses a qualitative descriptive method. As a result, many employees do not understand the HR function. So, it needs to be equipped with education or training on an ongoing basis, in order to improve the quality of work.